The Role of Bhabinkamtibmas Through Counseling Guidance in Preventing Crime of Theft With Aggravated Circumstances in the Legal Territory of the Klaten Police - Sulthon Sekar Jagat (Advances in Police Science Research Journal, 2021)
This research is motivated by non-criminal cases of theft with weights being the highest criminal cases, and experiencing a significant increase every year in the jurisdiction of the Klaten Police. The Klaten Police took action to prevent the crime of theft by weighting by implementing counseling guidance carried out by Bhabinkamtibmas. The purpose of this study is to determine the role of Bhabinkamtibmas, the factors, and the efforts made in the implementation of counseling guidance in preventing the crime of theft by weighting. Theories and concepts used in this research are management theory, Bhabinkamtibmas concept, counseling guidance, theft concept by weighting. This study uses a qualitative approach, with the type of field research, as well as data collection techniques by interviewing, observing and reviewing documents. Based on the results of the study, the authors found the fact that there were several things that had not been fulfilled in accordance with the provisions of the Chief of Police Regulation No. 21 of 2007 concerning Guidance on Counseling Public Order and Security. This is because the components in the planning, implementation, and analysis and evaluation stages have not yet been implemented. The implementation of counseling guidance by Bhabinkamtbmas is influenced by supporting factors and inhibiting factors described by management elements, namely Man, Money, Materials, Methods, Markets and Machines. The Klaten Police has also made efforts to increase the role of Bhabinkamtibmas. In connection with the results of the study, the authors provide input to Bhabinkamtibmas in conducting counseling guidance so that the delivery of material is more specific to the crime of theft with aggravated circumstances.